Multiple identities and crime: A study of Antillean women and girls in the Netherlands - Althoff, Martina (European Journal of Criminology, 2013)
The concept of intersectionality refers to the constructionist approach, which considers gender, class and race as categories of social inequality that cannot be added together but that intersect and construct each other. Social categories construct the social identities that affect what motivates people and how they operate. The question is how multiple identities come together in the context of crime? The paper reports the findings of a qualitative study that explored the concept of intersectionality when analysing crime. The study analysed the court files of Antillean women and girls living in the Netherlands and tried to find an explanation for their crime patterns in their struggle with their identity.
Keywords: antilles; approches et analyses; criminologie; discipline; europe; femmes* immigrantes; genre; identités LGBTQIA2+; identités de genre; intersectionnalité; inégalités; pays-bas; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppression; thématiques; violences; étude qualitative

L'ennemi principal. 1. Économie politique du patriarcat. - Delphy, Christine (Syllepse, 2013)
Qui est l’«ennemi principal»? Pour la féministe matérialiste qu’est Christine Delphy, il ne s’identifie ni à l’Homme – avec une majuscule –, ni aux hommes en général. Ce n’est en effet ni une essence ni un groupe naturel: c’est un système. Or ce n’est pas non plus, ou plutôt pas principalement, pour cette théoricienne qui s’inspire de Marx mais dans un parfait esprit d’hétérodoxie, le système capitaliste. L’ennemi principal, c’est ce qu’elle a choisi d’appeler le patriarcat : à savoir un système autonome d’exploitation et de domination. Christine Delphy a entrepris d’en constituer la théorie, très exactement l’économie politique du patriarcat. «L’ennemi principal», c’est aussi le titre de l’article de Christine Delphy qui, publié en 1970, la première année du Mouvement de libération des femmes, marque le début d’une révolution dans la réflexion féministe. Elle introduisait l’idée alors totalement nouvelle du patriarcat défini comme structure sociale hiérarchique et inégalitaire, en refusant toute explication de la subordination des femmes en termes idéalistes – que ce soit sur des bases biologiques, naturalistes ou essentialistes, ou bien encore fondées sur l’idéologie ou le «discours».
Donné en lecture cours FEM1000: "Avant-propos" p.5-30.
Keywords: 1900-1999; 1970-1979; approches et analyses; discipline; division sexuelle du travail; europe; fem1000; france; féminisme matérialiste; incontournable; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppression; violences

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppression; thématiques; émirats arabes unis; états-unis